Advanced control of synchronous reluctance machine drives - Krishnamurty, Anirudh Murthy (2019)
There is a huge demand for reducing carbon foot print from our day to day use. Automotive tail pipe emission being one of the major contributors to environmental pollutants. There is a huge push for clean energy resulting in development if Electric vehicle (EV) and Hybrid electric vehicle (HEVs). Since the primary mode of propulsion is electric vehicle is traction motors which is an electric machine hence, there is an increasing demand for high performance, highly efficient electric machines drive with increased power density and a very wide speed range. Recent trends in search for such a machine has made researchers notice on Synchronous reluctance motor and this also has kindled their interest to explore the design and control of such machines. Especially, in the domain of control due to its good torque and flux response direct torque and flux control (DTFC) has been quite common in the modern electric drives. But the torque and flux control are parameter dependent and thus there might be issues with the system stability and sluggish response when a conventional proportional integral controller. The control of flux and torque reference are obtained from the field Weakening (FW) and Maximum torque per Ampere (MTPA) block and then the error trajectory can be replaced from existing PI regulator with a Discrete Time Sliding mode control (DTSMC) to achieve a more robust control The proposed sliding mode control of SynRM comprises of design of two different sliding surface exclusively for torque and flux. An integral sliding surface is defined for the torque and flux errors and then discrete reaching laws are used for the convergence of the state variables to their reference values. The stability and convergence of this system is validated by using Lyapunov’s stability criteria. This work also involves deriving of the sliding surface in discrete domain from the discrete model of synchronous model and then the implementation of the discrete sliding mode control onto a MATLAB-SIMULINK model with the DTFC algorithm. The validity of constants used in the sliding mode reaching law and sliding surface definition are also verified through the simulation output.